Holocene climatic variability and historical anthropogenic impacts in the subarctic region : a multiproxy study of the sedimentary sequence of Lake Igaliku (Greenland) - Massa, Charly (CCSD, 2012)
The medieval Norse colonization of Greenland (986-1450 AD) and the subsequent reestablishment of agriculture in south Greenland, aided by recent climate warming, constitute a conceptual model that is particularly well adapted to understanding the relations between a community and its environment. In this perspective, a multi-parameter sedimentological study was undertaken on the sedimentary sequence of Lake Igaliku (N61°00’22”, W45°26’28”), situated in the heart of the medieval and current agricultural sector. The 4 m long sequence, covering the entire Holocene evolution of the lake (~10 000 years), was studied at high temporal resolution. The analyses included the physico-chemical characterization of the sediments (density, magnetic susceptibility, XRF, X-ray imaging, grain size, carbon, nitrogen, and sulphur content, ICP-AES, δ13C and δ15N isotopic ratios) as well as the biological components of the sediment (pollen, non-pollen palynomorphs, diatoms). 28 radiocarbon dates as well as 210Pb and 137Cs measurements created a precise temporal framework with which to reconstruct the postglacial evolution of the lake and its catchment in terms of isostatic constraints, climatic forcing and anthropogenic impacts. The first phase of basin evolution is primarily controlled by isostasy, with the rapid transition from glaciomarine conditions to a freshwater lake as the basin emerged from the fjord 9500 yr BP. Afterwards, the sedimentary sequence records the paleoclimatic evolution of the region. Paleolimnological and terrestrial proxies suggest an early warm phase likely interrupted by a cold, windy, dry period between 8600 yr BP and 8100 yr BP. A second dry, windy period between 5300 yr BP and 4800 yr BP predated the transition to neoglacial cooling, which is characterised at Igaliku by a switch to humid and perhaps cooler conditions after 4800 BP, and which caused a major shift in both aquatic and terrestrial ecology. Approximately 1000 AD, after the arrival of Norse settlers, the lacustrine system became ...